Citrus Fertilizer Management on Calcareous Soils - Thomas A. Obreza; Mongi Zekri; David V. Calvert (EDIS)
This document is about managing citrus fertilizer on calcareous soils, common in South Florida's flatwoods. Calcareous soils, with high calcium carbonate (CaCO3) content and alkaline pH levels, affect the availability of essential nutrients like nitrogen (N), phosphorus (P), magnesium (Mg), potassium (K), manganese (Mn), zinc (Zn), and iron (Fe). Effective nutrient management involves tailored strategies such as using ammoniacal fertilizers, foliar sprays, water-soluble P applications, and soil acidulents like elemental sulfur. By understanding and addressing the unique challenges of calcareous soils, citrus growers can enhance nutrient uptake and improve crop yields. First published Dec. 1993.